ASPEK HUKUM ZONASI PASAR TRADISIONAL DAN PASAR MODERN - Rahadi Wasi Bintoro (Faculty of Law, Universitas Jenderal Soedirman, 2010)
The existence of traditional markets in urban areas from time to time further increasingly threatened by rampant construction of modern markets. Therefore, in this paper the authors are interested to explore some aspects zoning laws of modern markets and traditional markets. Based on the analysis, zoning traditional markets and modern market is the authority of local governments as stipulated in Presidential Regulation Number 112 Year 2007 concerning Settlement and Development of Traditional, Modern Shopping Centers and who is the embodiment of Law No. 5 Year 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition healthy. If the establishment of a modern market violates the provisions of Law No. 5 Year 1999 and Presidential Decree. 112 Year 1999 will be reported to the KPPU to be examined.In addition, with no establishment of zoning district regulations regarding local government market has resulted in unlawful acts and therefore can be sued by actio popularis lawsuit or citizen law suits.Keywords: zoning, traditional markets, modern markets